PROBLEMATIKA PERKAWINAN WANITA HAMIL DAN IMPLEMENTASI KHI PASAL 53 TENTANG PERKAWINAN WANITA HAMIL DI PENGADILAN AGAMA. - Muhammad Sabir (Fakultas Syariah dan hukum Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
The marriage of a pregnant is a marriage that occurs before do marriage aqad. There have been differences of opinion among scholars regarding this marriage model. Even so, the State of Indonesia as a state based on law also regulates this marriage model which is contained in KHI article 53.The link between the marriage of a pregnant in a religious court is an application for marriage dispensation, because it is found that the requirements for submitting a marriage dispensation are for those who are constrained by the minimum age of marriage (19 years) with various reasons for filing including because of pregnancy. Various factors cause marriage of pregnant women, namely: age factors, lack of education, not understanding religious values and morality, as well as economic factors.